Alternative means to regulate the employment relationship in the changing world of work - Vettori, Maria-Stella (University of Pretoria, 2006)
Advancing technology has caused rapid and dramatic changes in the world of work. Labour law systems grounded in the industrial era, with their emphasis on collective bargaining, are not suitable in today’s world of work. Throughout the world, the ‘atypical employee’ is replacing the standard or typical employee whose terms and conditions of employment were generally regulated by collective agreements. Atypical employee’s terms and conditions of employment generally are not regulated by collective agreements. World– wide trends in the decentralisation of collective bargaining, decollectivisation and individualisation of the employment relationship have contributed to a decline in trade union power and influence. Consequently the number of workers covered by collective agreements has decreased. Collective bargaining has been rendered less effective because of the changing the world of work. The South African labour law system places a huge emphasis on collective bargaining, particularly at industry level, for the protection of employee interests. Given these trends in the changing world of work, the appropriateness of this emphasis on industry or central level collective bargaining is questioned. The vacuum left by the inadequacy and inability of trade unions to protect employee interests in a comprehensive manner by means of collective bargaining, needs to be addressed. The following alternative means of protecting employee interests are considered: (i) The socialisation of the law of contract; (ii) the interpretation given to the constitutional right to fair labour practices; and (iii) the role of good corporate governance and corporate social responsibility. These alternative means of addressing legitimate employee interests could play a role in filling the vacuum created by trade union decline. The South African law of contract is capable of bridging the gap between law and justice by the application of the concepts of good faith and public policy, so that employment contracts may take cognisance of employee interests despite the imbalance of power between employer and employee. The protection of worker interests by means of the constitutional right to fair labour practices depends on the judge’s interpretation of what is fair. Implementation of good corporate governance codes can be influential in protecting and promoting employee interests.
Keywords: Atypical employee; CSR; Collective bargaining; Corporate Social Responsibility; Corporate governance; Decentralization; Decollectivisation; Fordism; Individualization

The legal risks associated with trading in derivatives in a merchant bank - Terblanché, Janet René (University of Stellenbosch, 2006)
The research defines derivatives as private contracts, with future rights and obligations imposed on all parties, used to hedge or transfer risk, which derives value from an underlying asset price or index, which asset price or index may take on various forms. The nature of derivatives is that the instruments are intended to be risk management tools. The objectives of derivatives are either to hedge a risk, or to speculate. Derivatives may be classified by the manner in which they are traded, either over the counter (OTC) or on exchange. Alternatively, derivatives may be classified on the basis of structure and mechanisms, i.e. forwards, futures, options or swaps. Risk and risk management are defined in the third chapter with the focus on merchant banking. The nature of risk is that it is inherent in all activities. The nature of risk management is that it aims to ensure that the risks faced by the merchant bank are managed on a daily basis. The objective of risk management is to ensure that losses are minimised and the appropriate level of risk is taken in order to maximise profits. Risk may be classified as operational, operations, market, systemic, credit and legal risk. A comprehensive discussion of credit risk is presented, as it pertains to the legal risk in derivatives in a merchant bank. This includes insolvency, set-off, netting, credit derivatives and collateral. Legal risk is defined as the risk of loss primarily caused by legal unenforceability (i.e. a defective transaction, for instance a contract), legal liability (i.e. a claim) or failure to take legal steps to protect assets (e.g. intellectual property). The nature of legal risk is that it is caused by jurisdictional and other cross-border factors, inadequate documentation, the behaviour of financial institutions, a lack of internal controls, financial innovation or the inherent uncertainty of the law. The objectives of legal risk management in derivatives are to avoid the direct and indirect costs associated with legal risk materialising. This includes reputational damage. Derivatives attract specific legal risks due to the complexity of the instruments as well as the constant innovation in the market. There remains some legal uncertainty regarding derivatives in terms of gaming, wagering and gambling, as well as insurance. The relationship between risk and derivatives is that due to the complexity and constant innovation associated with derivatives, there are some inherent risks to trading in derivatives. It is therefore important to ensure that there is a vested risk management culture in the derivatives trading environment. Chapter four gives an overview of derivatives legislation in foreign jurisdictions and in South Africa. The contractual and documentation issues are discussed with reference to ad hoc agreements, master agreements and ISDA agreements. The practical implementation issues of master agreements and ad hoc agreements are also discussed. The recommendations are that legal risk management be approached in a similar manner to credit, market and other risk disciplines. A legal risk management policy needs to be developed and implemented. The second recommendation is that a derivative to manage the legal risk in derivatives be developed.

Re-Imagining International Law: An Examination of Recent Trends in the Reception of International Law Into National Legal Systems in Africa - Oppong, Richard (Fordham International Law Journal, 2006)
This article suggests that the trend of accepting the supremacy and direct application of international law represents a rethinking of the relationship between international and national law, and that its full implications are yet to be explored. The Article seeks to build on current writings on the subject by analyzing certain regional arrangements and judicial approaches relevant to, but often ignored in the discussion. It attempts not to situate these arrangements or approaches within or outside of the monist/dualist paradigm, but to assess the practical significance of these arrangements for international law, national law, and their respective subjects.

The Role of International Arbitrators - Franck, Susan D. (ILSA Journal of International & Comparative Law, 2006)

The Contractarian Model of Arbitration and Its Implications for Judicial Review of Arbitral Awards - Kirgis, Paul F. (Oregon Law Review, 2006)

Search and seizure, production and preservation of electronic evidence - Nieman, Annamart (North-West University, 2006)
Criminals are becoming increasingly involved in computing activity and connectivity, but practitioners in the criminal justice field do not seem to be keeping pace with crime in a computing context. Being comfortable with the technology that underpins the Information Age is a non-negotiable skill for those who have to unravel and bring twenty-first century crimes to book. Chapter two of this study therefore sought to serve two purposes. The first aim was to acquaint the reader with the exceedingly complex technologies involved in computers and networks. The second aim was to clarify the technical context and terminology typical of the collection of electronic evidence. South Africa signed the Cybercrime Convention in November 2001. At present, the Cybercrime Convention is the only existing internationally accepted benchmark, inter alia, for the procedural powers aimed at the collection of electronic evidence. The main objective of this study was to consider whether the South African search and seizure, production and preservation devices need to be augmented and/or aligned so as to be on par with the devices proposed in the Cybercrime Convention. This objective was served in two ways. Firstly, an exposition of the requirements, scope, conditions and safeguards of the domestic and transborder search and seizure, production and preservation mechanisms proposed by the Cybercrime Convention was provided in chapter three of this study. Secondly, an exposition of the domestic and transborder international search and seizure, production and preservation devices available in the current South African legislative framework was given in chapter four of this study. A comparative analysis was done between the South African catalogue of criminal procedural search and seizure, production and preservation devices compared to those set out in the Cybercrime Convention. Where any alignment or augmentation of the South African devices was found to be necessary, this study identified these intervention areas. The findings and recommendations based on this comparative analysis were set out in chapter seven of this study. In considering any alignments and/or augmentations required in respect of the South African domestic search and seizure, production and preservation mechanisms, the application of the equivalent mechanisms directed at electronic evidence used in the United States of America and England were investigated in chapters five and six respectively. The lessons learned were also referred to in chapter seven of this study.